Institute Medals and Prizes (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
INSTITUTE MEDALS AND PRIZES ASIDE from the John Fritz Medal, in which the Institute participates through its representation on the John Fritz Medal Board, the Institute itself has five major awards to make annually for excellence in technical papers, as follows The Robert W Hunt Medal, The Hadfield Prize, The J E Johnson Jr , Award, The Lewisohn Platinum Prize to senior members, and the President's Prize to junior members ROBERT W HUNT MEDAL The partners of Robert W Hunt established a fund which was presented to the Institute at a fitting ceremony on May 27, 1920, to establish an annual medal and a sum of money to be awarded under the following rules, 1 The award shall consist of two prizes, first of a gold medal, second of a sum of money, a certificate to accompany each prize The money prize shall not be awarded to a member over 40 years of age, but under unusual circumstances, both prizes may be allotted to one person provided that he is not over 40 years of age In general it will be understood that the Committee shall award the money prize to, the younger men, rather than the medal 2 The awards shall be made not oftener than once a year to that person or persons contributing to the Institute the best original paper or papers on iron and steel The scope of the term "iron and steel" shall be determined by the sub-committee consider¬ing the awards In general, papers dealing with the practical side of the subject have preference over those dealing with the theoretical side in recognition of the fact that Captain Hunt's main contributions to the industry have been in the improve¬ment of production and quality of material 3 A sub-committee of three to five, including the Chairman of the Iron and Steel Committee, shall be appointed by the Iron and Steel Committee annually to adjudge the award subject to approval 4 The awarding committee shall submit its report to the Iron and Steel Committee at its October Meeting, and the award be certified to the Secretary of the Institute in time to permit the presentation to be made at the Annual Meeting of the Institute 5 The recipient of the award shall be designated "The Hunt Medallist "